(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2026)
The paper contains a taxonomic description (added: including diagnosis and illustration) of a new species of slender crab-spider of the genus Tibellus Simon, 1875 from Bagerhat, Bangladesh. The species T. bagerhatensis n.sp. was identified as new to science. Generic diagnosis and distributions are also provided together with the description of the new species. J. Asiat. Soc. Bangladesh, Sci. 51(2): 223-232, December 2025